Side-Input GaAs Laser Power Converters With Gradient AlGaAs Waveguide - Khvostikov, Vladimir P.; Panchak, Alexander N.; Khvostikova, Olga A.; Pokrovskiy, Pavel. V. (IEEE electron device letters, 2022)
Vertical p-n junction photovoltaic converters are the subject of this work. In these devices, light is injected into the semiconductor crystal through a side interface. So the current-carrying contacts are continuous. Therefore, the advantages of this design compared to the traditional (horizontal p-n junction) are as follows: simplified post-growth processing and ease of sequential assembly. GaAs photovoltaic converters are of particular interest for converting the light with the wavelength of 850 nm. However, a prototype with a design completely similar to the horizontal one is inoperable due to high surface recombination. Waveguide can be implemented to get around this limitation. So photovoltaic converters with a vertical p-n junction with a GaAs active region and a 50~ μ \text{m} thick AlxGa1-xAs waveguide layer were grown by liquid-phase epitaxy. In the waveguide layer, laser radiation is refracted towards the active region without absorption. The refraction is provided by using a smooth linear change of x from 0.55 to 0.15. The grown samples were tested in practice under pulsed laser irradiation supplied by a 50~ μ \text{m} optical fiber. With the use of an antireflection coating on the photodetector interface, a photoconversion efficiency of 53% was shown at an irradiation power of 92 mW (4.7 kW/cm2) and more than 50% at 190 mW (10 kW/cm2).